1980
DOI: 10.1103/physreva.22.1906
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-flight study ofH(2S)andD(2S)produced by electron impact on

Abstract: Time-fhght spectra of H(2S) and D(2$) fragments from electron-bombardment dissociated H, and D, have been observed. Kinetic energy distributions of "fast" metastable fragments were obtained for electronbombardment energies ranging from near the threshold for fast metastable production {less than 29 eV) to 100 eV. At low bombarding energies previously unreported structure is observed in the fast peaks for both isotopes.At high bombarding energies also there is evidence of unresolved structure in the fast peaks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Thus many dissociation channels contribute to the fast atom dissociation process as predicted by Spezeski, Kalman, and McIntyre [4]. The steep rise in cross section beginning at 30 eV and the kinetic energy distribution energy dependence for fast fragments at 100 eV verifies that the dominant contribution to the fast H(2p) distribution arises from Qz ( Xg, II ) states as previously concluded for H(2s) [1,4].…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Thus many dissociation channels contribute to the fast atom dissociation process as predicted by Spezeski, Kalman, and McIntyre [4]. The steep rise in cross section beginning at 30 eV and the kinetic energy distribution energy dependence for fast fragments at 100 eV verifies that the dominant contribution to the fast H(2p) distribution arises from Qz ( Xg, II ) states as previously concluded for H(2s) [1,4].…”
supporting
confidence: 75%
“…The Balmer-u line profile, for example, shows a characteristic narrow central peak (-300 mA FWHM) and a broad wing ( - 1 [4] pointed out that the AP must be less than 27 eV, whereas Ogawa and Higo [10] measured thresholds of 24 and 27~1 eV for n = 4. In this work, we clearly identify three separate AP to~0.5 eV accuracy for the fast H(2p) atoms.…”
mentioning
confidence: 99%
“…Because the state was also known as the main contributor to the cross section for the H(2p) atom formation [16][17][18][19], the Q 2 1 u (1) state has been considered to dissociate into H(2s) + H(2p). However, this conclusion needs to be re-examined since (i) the theoretical potential energies and resonance widths of the doubly excited states of H 2 by the recent calculation with large configuration bases [6] differ from those by the former calculation [15] and (ii) the velocity distributions of H(2s) fragments depend on the electron impact energy [20], showing a possibility of contributions from the neutral and ionic molecular states other than the Q 2 1 u (1) state in the electron collision experiment by Misakian and Zorn. In the recent measurement of the cross sections for the H(2s) atom formation in photoexcitation of H 2 it was concluded that the contribution of the Q 2 1 u (1) state of H 2 was not so large [4,21] (see Fig.…”
Section: Introductionmentioning
confidence: 98%
“…To investigate the precursor doubly excited states resulting in the formation of H(2s) fragments it is necessary to measure the cross sections of the process as a function of excitation energy rather than the electron impact energy as was previously done [13,20]. As mentioned above, Glass-Maujean et al [21] measured cross sections for H(2s) formation in photoexcitation, σ 2s , of H 2 by using the detection technique based on the collision-induced emission of the Lyman-α photons [H(2s) + H 2 → H(1s) + H 2 + Lyman-α photon] in a gas cell filled with relatively high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical situation is somewhat more comfortable than its experimental counterpart, as can be observed in literature. Nevertheless, Spezeski et al [34] have achieved a complete study of the H 2 curves, even though the resolution of their spectra does not allow, for example, the separation of the slow H(2s) atoms. More recently Aoto et al [35] show evidence, beyond the Q 1 and Q 2 states, for the observation of Q 3 and Q 4 doubly-excited states.…”
Section: Fast H(2s) Atomsmentioning
confidence: 99%